Current trends in access to information: The case of flipboard as a content aggregator - De la Torre Díaz, Patricia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The online environment has conditioned the distribution and access systems to information. Four out of ten Internet users use a news aggregator and Flipboard is among the most used according to Reuters. We analyze its operation by comparing it with other existing options and interviewing its manager in Spain. Flipboard stands out as the only free aggregator with manual content curation. It is concluded that it may be necessary to adapt the work of the media to the new channels of access to information and educate society in their correct use.